Surveillance for Invasive Salmonella Disease in Bamako, Mali, From 2002 to 2018. (9th July 2020) - Still, William L; Tapia, Milagritos D; Tennant, Sharon M; Sylla, Mamadou; Touré, Aliou; Badji, Henry; Keita, Adama Mamby; Sow, Samba O; Levine, Myron M; Kotloff, Karen L
Abstract: Background: Salmonella enterica bloodstream infections are an important cause of childhood morbidity and mortality, including in Mali. We report 17 years of surveillance for nontyphoidal and typhoidal S. enterica infections among inpatients and outpatients at l'Hôpital Gabriel Touré, the main source of pediatric tertiary care in Bamako, Mali. Methods: Between June 2002 and December 2018, a blood culture was collected from 54 748 children aged ≤15 years with fever and/or suspected invasive bacterial infection who provided consent (38 152 inpatients, 16 596 outpatients). Bacterial pathogens were identified using standard microbiological techniques and serovars of S. enterica were determined by PCR and/or agglutination with antisera. Results: Nontyphoidal Salmonella (NTS) was identified in 671 enrolled inpatients (1.8% of all enrolled inpatients, 13.8% of enrolled inpatients with a positive culture). S . Enteritidis, the most common NTS serovar, accounted for 38.5% of all NTS isolates (n = 258), followed by S. Typhimurium (31.7%, n = 213). The median (SD) age of children with a culture positive for NTS was 1.8 (3) years. Overall case fatality was 20.9%. An additional 138 inpatients (0.4%) had a positive culture for typhoidal Salmonella . NTS was identified in 11 outpatients (0.07%), while typhoidal Salmonella was found in 49 outpatients (0.3%). The annual incidence of invasive NTS disease decreased over the study period, but case fatality remained high. Conclusions: Although incidence decreased, NTS remained a major cause of invasive bacterial infection and mortality among hospitalized children in Bamako, while typhoidal Salmonella was uncommon. Because 87% of NTS belonged to only 4 serovars, a multivalent vaccine may be an effective strategy to reduce the burden and mortality of invasive NTS.